Nurses' Knowledge, Beliefs and Practices towards Hand Hygiene - Tahereh Najafi Ghezeljeh; Zahra Abbasnejad; Forough Rafii; Hamid Haghani (Tehran University of Medical Sciences, 2015)
Background & Aim: Nurses' hands are important channels of micro-organisms transmission and hospital acquired infections. This study aimed to investigate knowledge, beliefs and practices of nurses regarding hand hygiene .   Methods & Materials: This was a cross-sectional study conducted in 2012. All nurses (n=282) working in three hospitals of Lorestan University of Medical Sciences participated in the study. Data were gathered using a demographic form, social desirability questionnaire, and hand hygiene knowledge, belief and practice questionnaire. Data were analyzed through descriptive and statistical tests (Independent t-test, ANOVA, Pearson Coefficient) in the SPSS-PC (v.21.0). The level of significance was set at below 0.05 .    Results: The mean scores of nurses' hand hygiene knowledge, beliefs and practices were 4.6±2.00, 3.8±0.40, and 4.33±0.50, respectively. Nurses washed their hands after contact with patients more often in compare with prior to contact with patient. There was a statistically positive and significant correlation between nurses' practice in required situations and nurses' beliefs regarding hand hygiene .   Conclusion: According to the results, nurses' knowledge regarding hand hygiene was low and hand hygiene practice in required situations was undesirable. Many nurses had negative and false beliefs regarding hand hygiene. Based on these results, it is necessary to plan programs to increase nurses' knowledge, belief and practice regarding hand hygiene .